Characteristics of classic style technique during starting phase in cross-country skiing - Fujita, Z.; Kinugasa, R.; Tauchi, K.; Tsuchiya. J. (Sport Science Research, 2011)
The purpose of this study was to clarify characteristics of double-poling (DP), diagonal stride (DIAG) techniques, and those combinations (COMB) during stating phase of cross-country-skiing. Five male cross-country skiers including the Japan national team performed sets of maximal effort of each three technique on flat and straight snow track. The motion was captured with the laser distance meter (Laveg-sports, Jenoptik) and high-speed camera (EX-F1, Casio). The time, mean and maximum velocities, number of cycle, cycle length and cycle rate were analyzed. Our result revealed the following: (1) required time of 50 m were not changed significantly among techniques. (2) maximum velocity was significantly higher in the DP than the DIAG. (3) although mean velocity was significantly higher in the DIAG during 10-20 m phase than the DP, the trend was changed during 30-50 m phase (DP > DIAG). (4) for the COMB trial, all subjects used the DIAG first, followed by the DP. Those results suggested that cross-country skier used the DIAG for acceleration, switched to the DP in order to achieving the maximum velocity, indicating interchange technique may play an important role for jump start from the early phase of competition.